HISTOMORPHOLOGICAL ALTERATIONS IN PANCREATIC ISLETS: EXPLORING THE STRUCTURAL DYNAMICS OF TYPE 2 DIABETES MELLITUS (Journal of Medical & Health Sciences Review, 2025)
The progression from insulin resistance to overt Type 2 Diabetes Mellitus (T2DM) is defined by the failure of pancreatic β-cells to compensate. While functional deficits are well-studied, comprehensive analysis of the concomitant structural alterations in pancreatic islets is crucial. This study aimed to perform a quantitative histomorphological assessment of pancreatic islets in a diet-induced murine model of T2DM to correlate structural changes with metabolic phenotype. The study conducted at Dr. Ruth K. M. Pfau, Civil Hospital Karachi where Twenty-four C57BL/6J male mice were allocated into two groups: a control group fed a normal chow diet (NCD, n=12) and an experimental group fed a high-fat diet (HFD, 45% kcal from fat, n=12) for 12 weeks. Metabolic profiling included weekly body weight, fasting blood glucose, and an intraperitoneal glucose tolerance test (IPGTT). Pancreatic tissues were processed for histology (H&E) and immunohistochemistry (anti-insulin, anti-glucagon). Morphometric analysis quantified islet density, individual islet area, β-cell area, and β-cell mass. HFD-fed mice developed significant obesity, hyperglycemia, and glucose intolerance (p < 0.01). Morphometrically, HFD islets exhibited a 52% increase in average islet area (p